2015
DOI: 10.14202/vetworld.2015.1364-1369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera on hematological parameters of calves reared in industrial fluorotic area

Abstract: Aim:The present study was undertaken to evaluate the ameliorative potential of dried Moringa oleifera fruit powder in fluorosis affected calves reared around the vicinity of aluminium smelter plant.Materials and Methods:Total 107 calves were screened on the basis of clinical signs and higher plasma fluoride (more than 0.2 ppm) level for evidence of fluorosis. Out of that, 90 samples found positive and from them 18 calves of 6-12 months age group were selected and divided equally into three groups named as Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
4
11
1
Order By: Relevance
“…The increase in the clotting time may be due to the fact that NaF is an anticoagulant and also chelates calcium ions from the blood, which is pre-requisite for blood clotting. Similar findings have been reported in buffalo calves [51] , [52] .…”
Section: Resultssupporting
confidence: 91%
“…The increase in the clotting time may be due to the fact that NaF is an anticoagulant and also chelates calcium ions from the blood, which is pre-requisite for blood clotting. Similar findings have been reported in buffalo calves [51] , [52] .…”
Section: Resultssupporting
confidence: 91%
“…But more significant increase in the above parameter along with TLC in tamarind supplementation group might be due to high iron and antioxidant like polyphenols and flavanoids, reported to be present in tamarind (Martinello et al, 2006). Similar reports of improved haematological parameters was also reported by Mandal et al, (2015) after feeding of Moringa oleifera fruit powder in fluorotic calves due to reduced fluoride load in plasma.…”
Section: Efficacious Treatment Of Tamarind For Ameliorating Fluorosis Compared To Boronsupporting
confidence: 66%
“…The presence of anemia in F-affected animals was also reported in calves (Bharti et al, 2007), buffaloes (Swarup and Singh 1989) and cows Swarup 1994 andMandal et al, 2015) whereas decrease in TLC was previously observed by Behera (1993) and Swarup and Singh (1989) in cattle. On the contrary, leucocytosis was observed in Finduced buffalo calves by Gill and Dumka (2013).…”
Section: Efficacious Treatment Of Tamarind For Ameliorating Fluorosis Compared To Boronsupporting
confidence: 57%
“…The usage of MO is known to have positive effects on some hematological parameters. This could be due to the phytochemical constituents in the extract and also presence of minerals and vitamins (Mandal et al, 2015). These constituents are well-known haemopoietic factors that have direct influence on the production of blood cells in the bone marrow.…”
Section: Hematologymentioning
confidence: 99%